Wavelength calibration and spectral sensitivity correction of luminescence measurements for dosimetry applications: method comparison tested on the IR-RF of K-feldspar - Sontag-González, Mariana; Mittelstraß, Dirk; Kreutzer, Sebastian; Fuchs, Markus (Radiation measurements, 2022)
Spectroscopic investigations provide important insights into the composition of luminescence emissions relevant to trapped-charge dating of sediments. Accurate wavelength calibration and a correction for the wavelength-dependent detection efficiency of the spectrometer system are crucial to ensure the correct spectrum interpretation and allow for its comparison with those obtained from other systems. However, to achieve an accurate detection efficiency correction, it is necessary to obtain the device-specific spectral response function (SRF). Here, we compare two SRF approximation methods by using either a calibration lamp of known irradiance or calculating the product of efficiency curves provided by the manufacturers of all known optical elements. We discuss the results using radiofluorescence (RF) measurements of two K-feldspar samples as an example. ...
Gesehen am 15.11.2023